Lrig1+ gastric isthmal progenitor cells restore normal gastric lineage cells during damage recovery in adult mouse stomach. Issue 9 (16th August 2017) - Choi, Eunyoung; Lantz, Tyler L; Vlacich, Gregory; Keeley, Theresa M; Samuelson, Linda C; Coffey, Robert J; Goldenring, James R; Powell, Anne E
Abstract : Objective: Lrig1 is a marker of proliferative and quiescent stem cells in the skin and intestine. We examined whether Lrig1-expressing cells are long-lived gastric progenitors in gastric glands in the mouse stomach. We also investigated how the Lrig1-expressing progenitor cells contribute to the regeneration of normal gastric mucosa by lineage commitment to parietal cells after acute gastric injury in mice. Design: We performed lineage labelling using Lrig1-CreERT2/+;R26R-YFP/+ (Lrig1/YFP) or R26R-LacZ/+ (Lrig1/LacZ) mice to examine whether the Lrig1-YFP-marked cells are gastric progenitor cells. We studied whether Lrig1-YFP-marked cells give rise to normal gastric lineage cells in damaged mucosa using Lrig1/YFP mice after treatment with DMP-777 to induce acute injury. We also studied Lrig1- CreERT2/CreERT2 (Lrig1 knockout) mice to examine whether the Lrig1 protein is required for regeneration of gastric corpus mucosa after acute injury. Results: Lrig1-YFP-marked cells give rise to gastric lineage epithelial cells both in the gastric corpus and antrum, in contrast to published results that Lgr5 only marks progenitor cells within the gastric antrum. Lrig1-YFP-marked cells contribute to replacement of damaged gastric oxyntic glands during the recovery phase after acute oxyntic atrophy in the gastric corpus. Lrig1 null mice recovered normally from acute gastric mucosal injury indicating that Lrig1 protein is not required for lineage differentiation. Lrig1+ isthmal progenitor cells did not contribute to transdifferentiating chief cell lineages after acute oxyntic atrophy. Conclusions: Lrig1 marks gastric corpus epithelial progenitor cells capable of repopulating the damaged oxyntic mucosa by differentiating into normal gastric lineage cells in mouse stomach.